Anthropometric indicators associated with blood pressure elevation in adults with obesity (Acta Scientiarum. Health Sciences, 2020)
The aim of the study was to investigate the association between different anthropometric indicators and high blood pressure in adults with obesity.This is a cross-sectional study with a non-probabilistic sample of adults with obesity. Systolic and diastolic blood pressure were measured using automated equipment (OMRON, model 742 HEM). The anthropometric indicators used were body mass index (BMI), relative fat mass (RFM), waist circumference (WC), waist-to-stature ratio (WSR) and waist-hip ratio (WHR). The data were analyzed by crude and adjusted (sex and age) linear regression, adopting a level of significance p